Pathway Analysis of the Heat Shock Protein 70 (HSP70) Gene in Some Selected Ruminants - Jacob M.; Dauda A.; Wafar R. J. (Darul Yasin Al Sys, 2026)
Heat stress poses a major challenge to livestock production, particularly in tropical regions, by threatening animal welfare and productivity; however, pathway-level understanding of the Heat Shock Protein 70 (HSP70) gene across ruminant species remains limited. This study investigated the molecular interactions and regulatory networks of the HSP70 gene under stress conditions in three economically important ruminants—Bos taurus, Ovis aries, and Capra hircus. A bioinformatic pathway analysis was conducted using 34 HSP70 gene sequences retrieved from the NCBI GenBank database, comprising 13 goat, 12 cattle, and 9 sheep sequences. KEGG and STRING databases were employed for pathway enrichment and protein–protein interaction analysis, with confidence scores greater than 0.700 used to define interactions. The results showed that HSP70 functions as a central molecular hub integrating three major biological pathways: the MAPK stress response cascade, the TLR4-mediated innate immune pathway, and the apoptosis regulation pathway. A conserved chaperone cascade involving HSPA1A/HSPA1B/HSPA1L, DNAJB1, HSP90, and HSP70 was identified across all three species, indicating evolutionary conservation of thermotolerance mechanisms. Protein–protein interaction analysis further positioned HSP70 at the center of interactions with co-chaperones such as HSP90, HSP40, DNAJB1, BAG3, and STIP1, forming a coordinated multi-protein repair system. Its anti-apoptotic role was evident through inhibition of caspase activation, suppression of pro-apoptotic BAX activity, and stabilization of anti-apoptotic BCL2. Comparative analysis revealed substantial conservation of pathway architecture among the three species, with only slight variations in the heat shock gene cascade order that may reflect species-specific stress responses. This study provides a comprehensive molecular framework for understanding HSP70-mediated thermotolerance in ruminants and identifies potential genetic targets for marker-assisted selection and genomic breeding strategies to enhance climate resilience and support sustainable livestock production under changing climatic conditions.